Facial skin rejuvenation with poly-l-lactic acid (PLLA): Four case studies - Setiawan, Stanley; Handayani, Theressia; Luziani, Stefani (UI Scholars Hub, 2024)
Background: Facial aging is characterized by the decline and loss of skin structure. Poly-l-lactic acid (PLLA) is a biopolymer and biodegradable injection material that functions as a collagen stimulator. This active ingredient works by stimulating the formation of skin collagen after interacting with the PLLA crystal component. The expected final result is an increase in the skin volume with the thickening and increased density of the skin layers due to collagen remodeling. At present, data on the application of PLLA for facial photorejuvenation remains limited. Case Illustration: Four patients aged 22-49 years old, with different severity of aging, underwent PLLA injection procedures. The active component was administered through injection with a dilution ratio of 1:1 to 1:2 for the cheeks and temporal area and without dilution for the forehead, smile lines, and chin area. After the injection, a gentle massage was performed, and the patient was instructed to self-massage every day. Each patient was evaluated on the twentieth day and underwent additional injection sessions up to two times. Discussion: All patients showed improvement as assessed using photography and the Global Aesthetic Improvement Scale (GAIS) 20 days after the procedure. All patients were satisfied with the final result. There was no significant pain during the procedure. Conclusion: PLLA injection is a safe and effective procedure that stimulates the formation of new collagen adequately. Patient satisfaction with the treatment was excellent, and no complications were observed in all patients.